Anthropometric chair design using the reverse engineering method to support practical learning - Haryo Sutedi; Nensi Yuselin; Neilinda Novita Aisa; Edwar Rosyidi; Rifdah Zahabiyah; Yuliani Fauziah; Indra Setiawan; Agusti Alvi Farhan; Ghiyas Ijaz Muffazal; Jason Bagasputra Setyawan; Muhammad Irham Amirul Hakim; Arif Mursyid; Erlangga Satria; Muhammad Padillah; Sofyan Effendi (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
Accurate measurements are essential to ensure tool alignment, machine precision, and measurement results. Currently, there is a difference in the height of students at the Astra Polytechnic, therefore an anthropometric chair is needed to facilitate the measurement of body dimensions. Anthropometric chairs are specialized tools for measuring body dimensions, but there are often some problems in their use. To overcome this problem, improvements are made through the Reverse Engineering method which aims to reproduce or recreate an existing model without using the original design documents. The main goal of this study is to improve the efficiency and accuracy of measuring students' body dimensions. These modified anthropometric chairs are expected to be easier to use, with an easily adjustable height and a simple disassembly and assembly process. The improved results show that the new design of the anthropometric chair is more efficient and improves the accuracy of measurement results, as well as providing more reliable data for a variety of purposes, such as product design and ergonomic studies.